Enhancing the performance of biogeography-based optimization using polyphyletic migration operator and orthogonal learning - Xiong, Guojiang; Shi, Dongyuan; Duan, Xianzhong (Computers & operations research, 2014)
Biogeography-based optimization (BBO) is a powerful population-based algorithm inspired by biogeography and has been extensively applied to many science and engineering problems. However, its direct-copying-based migration and random mutation operators make BBO possess local exploitation ability but lack global exploration ability. To remedy the defect and enhance the performance of BBO, an enhanced BBO variant, called POLBBO, is developed in this paper. In POLBBO, a proposed efficient operator named polyphyletic migration operator can formally utilize as many as four individuals’ features to construct a new solution vector. This operator cannot only generate new features from more promising areas in the search space, but also effectively increase the population diversity. On the other hand, an orthogonal learning (OL) strategy based on orthogonal experimental design is employed. The OL strategy can quickly discover more useful information from the search experiences and efficiently utilize the information to construct a more promising solution, and thereby provide a systematic and elaborate reasoning method to guide the search directions of POLBBO. The proposed POLBBO is verified on a set of 24 benchmark functions with diverse complexities, and is compared with the basic BBO, five state-of-the-art BBO variants, five existing OL-based algorithms, and nine other evolutionary algorithms. The experimental results and comparisons demonstrate that the polyphyletic migration operator and the OL strategy can work together well and enhance the performance of BBO significantly in terms of the quality of the final solutions and the convergence rate. •An enhanced BBO variant (POLBBO) is developed for solving global numerical optimization problems.•A polyphyletic migration operator is proposed to generate new features from more promising areas in the search space.•An OL strategy is employed to provide a systematic reasoning method to guide the search directions of POLBBO.•The polyphyletic migration operator and the OL strategy can work together well and enhance the performance of BBO significantly.•Five state-of-the-art BBO variants, five existing OL-based algorithms, and nine other evolutionary algorithms are employed to compare.